Social functioning of children with disabilities - Zięba, Ewa; Zięba, Paulina; Papierz, Justyna; Nowak-Starz, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Nowadays the society aims at improving the sense of well-being. Increasingly, it is observed that the problem of functioning of the disabled in the society is underestimated. Disabilities and handicaps are quite common social phenomena, so it is vital to help people with disabilities and create favourable living conditions for them in the society. Aim of the study. The purpose of the study is to determine the degree of difficulty in their functioning and to evaluate of the possibility of introducing changes which would improve the quality of life of children with disabilities in the community in Świętokrzyskie Voivodeship. Material and methods. The study involved 25 families with 27 children’s disabilities living in urban and rural areas in Świętkokrzyskie Voivodeship. The research was conducted from June 2013 to February 2013 in the Świętokrzyskie Voivodeship among parents and guardians of children with disabilities. The study was conducted using the method of diagnostic survey based on the author’s questionnaire consisting of 15 closed questions. Results. The results of the research include subjective opinions of guardians on the children’s disabilities and specific issues related to them. Parents believe that the authorities’ actions for the disabled are very limited. Families receive support from people having a similar situation or from the relatives. Conclusions. The degree of difficulty in functioning of children with disabilities in the society is high. The prospective change of the current approach to disability for the better is very unlikely because it is the human mentality that lies at the basis of the change.